Pelaksanaan Autonomi Pasien Dalam Persetujuan Informed Consent di Rumah Sakit - Musdalifah Musdalifah; Amir Suliati; Irwan Andi Alamanda; Dwimartyono Fendy; Dahlia Dahlia (Rumah Sakit Ibnu Sina, Makassar, 2021)
The regulation of the minister of health Number: 290/Menkes/Per/III/2008 it is stated that informed consent is an agreement that has been given by the patient or patient's relatives after receiving a complete explanation of the medical treatment to be carried out to the patient. Informed consent is very important to the doctor-patient relationship. The practice of obtaining patient consent for clinical decisions stems from the principle of autonomy. This literature review aims to determine the description of the implementation of patient autonomy in informed consent in hospitals. This type of research uses a Literature Review with a Narrative Review design. The results of the literature show the implementation of informed consent in hospitals, namely the type of information that is given the most about disease diagnosis, complications, procedures for action, goals, risks of action, prognosis, while the least is about alternative actions and costs. The implementation of informed consent is not fully implemented properly. The patient and the patient's family understand the delivery of information about the diagnosis of the disease, the procedure of action, and the risks of the action, however, this is different for the patient/patient family who does not understand about alternative actions.